Self-similar asymptotics in convergent viscous gravity currents of non-newtonian liquids - Gratton, J. (2009)
We investigate the evolution of the ridge produced by the convergent motion of two substrates, on which a layer of a non-Newtonian power-law liquid rests. We focus on the self-similar regimes that occur in this process. For short times, within the linear regime, the height and the width increase as t 1/2, independently of the rheology of the liquid. In the self- similar regime for large time, the height and the width of the ridge follow power laws whose exponents depend on the rheological index. © 2009 IOP Publishing Ltd.